Playing in isolation : a history of baseball in Taiwan - Yu, Junwei (University of Nebraska Press, 2007)
Despite the political instability characterizing twentieth-century Taiwan, the value of baseball in the lives of Taiwanese has been a constant since the game was introduced in 1895. The game first gained popularity on the island under the Japanese occupation, and that popularity continued after World War II despite the withdrawal of the Japanese and an official lack of support from the new state power, the Chinese Nationalist Party.